2004
DOI: 10.1111/j.1365-2400.2004.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Coupling insights from a carp, Cyprinus carpio, angler survey with feeding experiments to evaluate composition, quality and phosphorus input of groundbait in coarse fishing

Abstract: A carp angler survey indicated that specialised carp anglers used on average 215 kg groundbaits (mostly cereals, nuts, beans, boilies) per year which corresponded to a mean annual gross P-input of 1018 g P angler )1 . A feeding experiment was conducted with juvenile carp fed with a random sample of the main bait types used in coarse angling to estimate the nutritional quality and P-retention efficiency. The investigated groundbaits had a rather low nutritional quality. Based on the examined P-retention efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 24 publications
2
59
1
Order By: Relevance
“…Although some studies have addressed groundbaiting (e.g., Wolos et al 1992, Niesar et al 2004, Arlinghaus and Niesar 2005, Lewin et al 2006, we found no previous research that applied the modeling of reservoir water quality with simulations related to groundbaiting. We integrated SWAT (Neitsch et al 2002) …”
contrasting
confidence: 39%
See 1 more Smart Citation
“…Although some studies have addressed groundbaiting (e.g., Wolos et al 1992, Niesar et al 2004, Arlinghaus and Niesar 2005, Lewin et al 2006, we found no previous research that applied the modeling of reservoir water quality with simulations related to groundbaiting. We integrated SWAT (Neitsch et al 2002) …”
contrasting
confidence: 39%
“…Ordinary commercial groundbait is composed mainly of flours (e.g., corn, peanut, wheat), bread crumbs and crackers, aromatics, and dyes, in different proportions depending on the target species. Some studies indicate that the use of groundbait can negatively affect water quality and trophic status, cascading to other ecosystem components such as invertebrates (Wolos et al 1992, Niesar et al 2004, Arlinghaus and Niesar 2005, Lewin et al 2006. Nutrient enrichment of waterbodies and the consequent eutrophication effects are major problems for water quality in reservoirs (Smith et al 1999, Carpenter andLathrop 2008).…”
mentioning
confidence: 99%
“…Whilst the quantity of fishmeal pellets that were introduced into each river was not quantified, for comparative purposes it has been estimated that recreational anglers in Germany introduced a total of 24,000 tonnes of angling bait into freshwater fisheries in 2004 (Arlinghaus and Niesar 2005). This was not only believed to represent a significant trophic subsidy for the fish, but also elevated nutrient concentrations in the water and subsequently impacting adversely on water chemistry (Niesar et al 2004;Arlinghaus and Niesar 2005;Lewin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Carp feed on such food through a fast and voluminous expansion of the oropharyngeal and opercular cavities that causes a suction flow facilitating the uptake of particulate food such as corn from a distance within the headlength of the fish (Sibbing, 1988). Presumably, carp in the present study were preconditioned to feed on corn as corn was also offered as groundbait and thus was available in large numbers at the fishing site because this is typical in specialised carp angling (Arlinghaus and Mehner, 2003;Niesar et al, 2004;Arlinghaus and Niesar, 2005). Accordingly, carp might have adjusted the suction strength to the weight of the corn.…”
Section: Discussionmentioning
confidence: 97%